Strengthening Civil Servant Engagement in Sustainable Development - Asti Amelia Novita; Gi-Heon Kwon; Suhartono Winoto (University of Merdeka Malang, 2026)
Examines the influence of leadership, employee understanding, and employee motivation on the engagement of Civil Servants (ASN) in supporting the Sustainable Development Goals (SDGs) within Regional Device Organizations (OPD). The SDGs represent a global agenda to address complex development challenges, and ASN engagement is crucial for their implementation. This study employs a quantitative approach using Structural Equation Modeling (SEM) techniques to evaluate the relationships among these variables. The analysis results indicate that leadership and employee understanding have a significant impact on ASN engagement, while employee motivation does not show a significant influence. The measurement model reveals that the indicators of leadership and employee understanding variably contribute to their latent variables, while the indicators of employee motivation are inconsistent in their effects. These findings emphasize the importance of effective leadership and a good understanding of the SDGs in enhancing ASN engagement, as well as highlighting the need for further evaluation of other factors that may influence this engagement. This research contributes both theoretically and practically by providing insights into strategies for enhancing ASN engagement in sustainable development programs.